Modern understanding of the pathogenesis of basal cell skin cancer - R. R. Saytburkhanov; A. A. Kubanov; I. N. Kondrakhina; X. I. Plakhova (State Scientific Center of Dermatovenereology and Cosmetology, 2021)
The incidence of basal cell skin cancer is increasing worldwide. The initiation and progression of basal cell skin cancer is due to the interaction of environmental factors and the patient's genetic characteristics. Aberrant activation of the transmission of the Hedgehog signaling pathway is the main pathogenetic pathway of carcinogenesis. Since basal cell skin cancer is manifested by significant variability of morphological structure, aggressiveness and response to treatment, the disclosure of the molecular genetics of pathogenesis will become the basis for developing new approaches and increasing the effectiveness of treatment, as well as overcoming tumor resistance to treatment. To search for the necessary literature, the PubMed, MedLine, Web of Science and RSCI databases were used.